2017
DOI: 10.4236/ojf.2017.71005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tree Stump Harvesting on Soil Carbon and Nutrients and Second Rotation Tree Growth in Mid-Wales, UK

Abstract: The drive to develop renewable energy is increasing the interest in energy forestry. Woody biomass from forest residues has the potential to make a significant contribution to greenhouse gas emission reduction through fossil fuel substitution. However, there is a danger of operational practice running ahead of the understanding of the environmental impacts of such activities. Consequently, there is an urgent requirement for scientifically underpinned guidance on the best management practices to ensure soil and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
5
1
1
Order By: Relevance
“…In contrast to most other European studies, Vanguelova, Pitman, Benham, Perks, and Morison (2017) reported dramatic losses of SOC 4 years after stump harvesting in mid-Wales. Unfortunately, for the conclusion, the main plots were not replicated, and the differences reported can thus also depend on initial plot differences.…”
Section: Field Experiments Outside the Nordic Countriescontrasting
confidence: 90%
“…In contrast to most other European studies, Vanguelova, Pitman, Benham, Perks, and Morison (2017) reported dramatic losses of SOC 4 years after stump harvesting in mid-Wales. Unfortunately, for the conclusion, the main plots were not replicated, and the differences reported can thus also depend on initial plot differences.…”
Section: Field Experiments Outside the Nordic Countriescontrasting
confidence: 90%
“…Forest harvesting has been shown to lead to soil acidification (Vanguelova et al, 2010, Vanguelova et al, 2017, and therefore the lower pH values in the abandoned coppice stand may be related to past management. However, this explanation is not supported by the fact that the upper soil layer (pH 5.50 and 5.70 in high and coppiced stands, respectively) in both types of forest stand was less acidic than the deeper layers, as the upper layer of coppice forest should be more acidic and of similar pH to the underlying soil layers.…”
Section: Discussionmentioning
confidence: 99%
“…UK guidelines are the most in-depth and note that forest harvest residue removal may lead to reduced soil C storage [73] but a "lack of empirical data makes it difficult to predict the impact of stump removal on the exchange of CO 2 and other greenhouse gases for different soil types" [81]. Guidelines suggest that the amount of soil C lost will increase with soil C content, which is reinforced by stump harvesting trial results [82,83]. More recent UK guidelines [34,67] recommend biomass retention to minimize C loss from sites, and this is consistent with guidance for maintaining soil productivity (e.g.…”
Section: Carbon Emissions and Sequestrationmentioning
confidence: 99%